Whole genome analysis of Human Mastadenovirus D causing Keratoconjunctivitis in India - A multicentre study - Ferdinamarie S Philomenadin; Mini P Singh; Jayanthi Shastri; Anil C Phukan; Muruganandam Nagarajan; Subashini Kaliaperumal; Radha Kanta Ratho; Jagat Ram; Madhav J Sathe; Avinash Ingole; Darshana B Rathod; Benjamin Nongrum; et al. (Journal of Infection in Developing Countries)
Introduction: Human mastadenovirus (HAdV) types 8, 37, 64 have been considered the major contributors in Epidemic keratoconjunctivitis (EKC) epidemics, but recent surveillance data have shown the involvement of emerging recombinants, including HAdV-53, HAdV-54, and HAdV-56. In our initial work, positive samples for adenovirus revealed that our strains were closer to HAdV-54 than HAdV-8. Hence, the current study aimed to use whole genome technology to identify the HAdV strain correctly.